An innovative method of Diaspis echinocacti Bouche control using DNA insecticide onOpuntia ficus-indica (L.) Mill. in the Nikitsky Botanical Garden, Crimea - Yu. V. Plugatar; E. S. Chichkanova; E. V. Yatskova; A. K. Sharmagii; V. V. Oberemok (Юг России: экология, развитие, 2021)
Aim. Investigation of the effectiveness of a DNA insecticide with a high level of environmental friendliness on Diaspis echinocacti Bouche in the greenhouse of the Nikitsky Botanical Garden.Materials and Methods. The object of the study was the insect pest Diaspis echinocacti Bouche. The number of D. echinocacti larvae was identified on segments of Opuntia ficus-indica L. (Mill.) using a Nikon SMZ 745T microscope and computer microphotography. In the experiment, the effectiveness of the DNA insecticide "Cactus-NBG" on D. echinocacti was studied, the preparation "Tanrek VK", VRK, from the class of neonicotinoids being used as a standard insecticide.Results. It was revealed that the treatment with the DNA insecticide "Cactus-NBG" against D. echinocacti larvae had a significant insecticidal effect. The biological effectiveness of the preparation was 82.0%. The mortality of larvae after treatment significantly increased in comparison with the control (p<0.05) and was measured at 43.2±5.0%, 53.2±2.3%, and 84.2±2.2% on the 3rd, 7th, and 14th day after treatment respectively.Conclusion. As a result of treatment of O. ficus-indica against D. echinocacti with the contact DNA insecticide "Cactus-NBG", a significant insecticidal effect was found. On the 14th day after treatment, the mortality of D. echinocacti in "Cactus-NBG" was 84.2±2.2%, in the "Tanrek" group - 86.0±1.4% and in the control group treated with water -11.2±1.2%. The biological effectiveness of "Cactus-NBG" on the 14th day was 82.0%. Thus, the preparation "Cactus-NBG", based on the antisense fragment of the D. echinocacti genome, caused a significant mortality of the target insect pest and can compete with modern chemical preparations.